2020
DOI: 10.1177/1071100720962796
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Arthroscopic and Radiographic Findings of Deep Deltoid Ligament Injuries in Rotational Ankle Fractures

Abstract: Background: The deep deltoid ligament (DDL) is a key stabilizer to the medial ankle and ankle mortise and can be disrupted in ligamentous supination external rotation type IV (LSER4) ankle fractures. The purpose of this study was to define the medial clear space (MCS) measurement on injury mortise radiographs that corresponds with complete DDL injury. Methods: A retrospective record review at a level 1 hospital was performed identifying patients with LSER4 ankle fractures who underwent arthroscopy and open red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The deltoid ligament plays a major role in limiting talar abduction, pronation, and external rotation, thus protecting the syndesmosis and the distal fibula. 2,5,8,19,41,43,49 Their combined injuries are therefore frequent. 34,51 Consideration of a DPTTL lesion associated with syndesmosis injury is important because it leads to external rotation of the tibiotalar joint, worsening the instability in favor of operative management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The deltoid ligament plays a major role in limiting talar abduction, pronation, and external rotation, thus protecting the syndesmosis and the distal fibula. 2,5,8,19,41,43,49 Their combined injuries are therefore frequent. 34,51 Consideration of a DPTTL lesion associated with syndesmosis injury is important because it leads to external rotation of the tibiotalar joint, worsening the instability in favor of operative management.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the clinical examination or arthroscopic examination, 2,35 magnetic resonance imaging is the gold standard for imaging ankle ligaments. 37 Another cross-sectional imaging alternative is the computed tomographic scan, which has shown its usefulness in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 A study of supination–external rotation type 4 ankle fracture reported that patients with arthroscopic evidence of partial deep DL injury had a radiographic MCS ranging from 4.0 to 5.0 mm on injury mortise view, and patients with complete deep DL injury had an MCS ranging from 5.5 to 29.9 mm. 1 In addition to deep DL injury, arthroscopy could be used to diagnose superficial DL disruption by passing a probe from the medial gutter around the anterior colliculus into the subcutaneous tissue, which cannot be accomplished with the use of stress radiography only.…”
Section: Discussionmentioning
confidence: 99%
“…First, the average age of cadaveric specimens is older than that of patients suffering from DL injuries with ankle fractures, which is a common bias for in vitro cadaveric specimens because of their limited availability. 1,7 Second, the technique for probing into the medial gutter for MCS measurement may be subject to intersurgeon variability, which may result in bias. In our study, the 2 operators were instructed to advance the probe gently without obvious damage to surrounding cartilage.…”
Section: Discussionmentioning
confidence: 99%